2012
DOI: 10.1002/hyp.9631
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of suspended sediment in Meltwater from Glaciers of Garhwal Himalaya

Abstract: Glacierised basins are significant sources of sediments generated by glacial retreat. Estimation of suspended sediment transfer from glacierised basins is very important in reservoir planning for hydropower projects in Himalaya. The present study indicates that storage and release of sediment in proglacial streams may categorise the pattern of suspended sediment transfer from these basins. Assessment of suspended sediment concentration (SSC), suspended sediment load (SSL) and yield has been undertaken for Duna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Other stations in the UGB such as Chorabari, Gangotri, and Dunagiri glaciers at the same elevation (~3,800 m asl) illustrate similar trends. Chorabari Glacier, which is in close proximity, receives approximately the same amount of rainfall (Kumar et al, ), whereas Gangotri (~269 mm) and Dunagiri glaciers (~231 mm) are in a rain shadow region and receive lower rainfall amount (Kumar, ; Srivastava et al, ), indicating that the amount of rainfall varies spatially, though the source of rainfall remains same. Thus, implying that rainfall is highly variable both spatially and temporally in the region and microclimatic studies is also important for understanding the hydroclimatic processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other stations in the UGB such as Chorabari, Gangotri, and Dunagiri glaciers at the same elevation (~3,800 m asl) illustrate similar trends. Chorabari Glacier, which is in close proximity, receives approximately the same amount of rainfall (Kumar et al, ), whereas Gangotri (~269 mm) and Dunagiri glaciers (~231 mm) are in a rain shadow region and receive lower rainfall amount (Kumar, ; Srivastava et al, ), indicating that the amount of rainfall varies spatially, though the source of rainfall remains same. Thus, implying that rainfall is highly variable both spatially and temporally in the region and microclimatic studies is also important for understanding the hydroclimatic processes.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of studying glaciers has considerable significance in context of anthropogenic global warming because of their climate sensitivity. Several studies worldwide have shown the importance of meteorological variables in understanding the behaviour of glacier retreat, mass balance, melt runoff, sediment transport, and so on (Singh, Kumar, & Kumar, ; Srivastava, Kumar, Verma, & Swaroop, , ). Meteorological observations are also used in a number of physical models such as SNOWMOD, Spatial Processes in Hydrology (SPHY), and Snowmelt Runoff Model (SRM) for simulating and predicting future scenarios of glacier health, water availability, and so on (Martinec, Rango, & Roberts, ; Singh, Haritashya, & Kumar, ; Singh, Haritashya, Kumar, & Singh, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous investigations, the shape of the Discharge–SSC hysteresis loop presents different kinds of patterns (i.e. linear, clockwise, counter‐clockwise and digit‐eight) depending on the mechanisms underlying sediment transport processes (Kumar et al ., ; Singh et al ., ; Srivastava et al ., ; Sun et al ., ). From Singh et al .…”
Section: Resultsmentioning
confidence: 89%
“…Srivastava et al . () collected suspended sediment data near the snout of the Dunagiri glacier at an elevation of 4250 m a.s.l, with a length of 5.5 km and an area of 17.9 km 2 , at a time interval of 4 h for the entire ablation season. Assuming a reasonable flow velocity of 2 m/s, the water needed less than 1 h to run from the furthest end to the outlet of the watershed.…”
Section: Introductionmentioning
confidence: 99%